Augmented Reality Navigation-Assisted Laparoscopic Hepatectomy: A Retrospective Comparison of Anatomical and Non-anatomical Resection. - Xu, Haisong; Huang, Wenhao; Luo, Huoling; Zhang, An; Guo, Yuehua; Peng, Gongze; Wu, Tianchong; He, Yongzhu (Clinical Medicine Insights: Oncology, 2026)
Background: Augmented reality navigation (ARN) has been increasingly applied in laparoscopic liver surgery to improve anatomical orientation and surgical precision. However, its clinical value compared with conventional anatomical liver resection (ALR) and non-anatomical liver resection (NALR) remains unclear. Method: This retrospective single-center study included 96 patients with hepatocellular carcinoma who underwent laparoscopic hepatectomy from January 2019 to December 2021. Patients were divided into three groups: ARN-assisted laparoscopic nonanatomic hepatectomy (Group A, n=28), laparoscopic anatomical hepatectomy without navigation (Group B, n=35), and laparoscopic nonanatomic hepatectomy without navigation (Group C, n=33). Baseline demographic, clinical, tumor, and segmental distributions were comparable among groups. Postoperative outcomes, postoperative complications, and 36-month follow-up data were analyzed. Result: Preoperative characteristics did not significantly differ among the three groups. Operative time was significantly shorter in Group A than in Group B (p =0.003) and Group C (p =0.039). Median intraoperative blood loss in Group A was 125ml, which was 175ml less than in Group B (p =0.048) and 75 ml less than in Group C (p =0.049). On postoperative day 7, median α-fetoprotein was lower (p= 0.049) in group A (4.26 iu/ml) than in group C (5.82 iu/ml). 3-Year overall survival did not significantly differ among three groups. 3-Year tumor-free survival rates were 60.7% in group A, 62.9% in group B, and 36.3% in group C, with Group A and B showing significantly better tumor-free survival than group C ( p (A v s. C) = 0.041; p (B v s. C) = 0.024). Postoperative complication rates were similar across groups. Conclusion: In this cohort, ARN-assisted laparoscopic nonanatomic hepatectomy was associated with reduced operative time and blood loss and demonstrated short-term oncological outcomes similar to anatomical hepatectomy. These findings suggest that ARN may enhance the effectiveness of non-anatomical hepatectomy; however, confirmation in larger prospective studies is required.